2020
DOI: 10.1093/jas/skaa278.635
|View full text |Cite
|
Sign up to set email alerts
|

PSV-31 Influence of Hempseed Meal Supplementation on Fresh and Cooked Characteristics of Boer Cross Goats

Abstract: Hempseed meal is byproduct of hemp oil production and is relatively high in fiber, fat, and protein, making it a potential feedstuff for ruminants. However, the impact this new byproduct could have on meat characteristics is unknown. The objective of the current study was to evaluate the impact of HSM on fresh and cooked characteristics of Spanish meat goat retail cuts. Forty Boer crossbred castrated male goats were randomly allocated to one of four diets (n = 10; 0, 10, 20 or 30%) containing HSM which origina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Previous research evaluating the effect of HSM on fresh and cooked characteristics of meat are extremely limited. However, Smith et al [ 20 ] reported no significant difference ( p > 0.05) on the fresh and cooked characteristics in the goat meat fed with varying levels of HSM. Limited research has been undertaken on the carcass characteristics of goat meat [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Previous research evaluating the effect of HSM on fresh and cooked characteristics of meat are extremely limited. However, Smith et al [ 20 ] reported no significant difference ( p > 0.05) on the fresh and cooked characteristics in the goat meat fed with varying levels of HSM. Limited research has been undertaken on the carcass characteristics of goat meat [ 21 ].…”
Section: Introductionmentioning
confidence: 99%